Concentrations of mercury and other trace elements in two offshore skates: sandy ray Leucoraja circularis and shagreen ray L. fullonica. Issue 1 (15th October 2017) - Nicolaus, E.E. Manuel; Barry, Jon; Bolam, Thi P.C.; Lorance, Pascal; Marandel, Florianne; McCully Phillips, Sophy R.; Neville, Suzanna; Ellis, Jim R.
Abstract: Trace metal concentrations in muscle and liver tissues from two offshore species of skate were examined. Concentrations of mercury in muscle of Leucoraja circularis (n = 20; 23–110.5 cm total length, 157–490 m water depth) and L. fullonica (n = 24; 28.5–100 cm total length, 130–426 m water depth) were 0.02–1.8 and 0.04–0.61 mg kg − 1, respectively. Concentrations of both As and Hg increased with total length. Only the largest specimen had a concentration of Hg in muscle > 1.0 mg kg − 1 . Data were limited for specimens > 90 cm long, and further studies on contaminants in larger-bodied skates could usefully be undertaken. Highlights: Analysed 11 trace elements in two tissues from two offshore skate species. Concentrations of mercury in muscle of Leucoraja circularis were 0.02–1.8 mg kg − 1 . Concentrations of mercury in muscle of L. fullonica were 0.04–0.61 mg kg − 1 . Concentrations of both As and Hg increased with total length. Only the largest specimen had a concentration of Hg in muscle > 1.0 mg kg − 1 .